ПРО ДЕЯКІ АСПЕКТИ ОРГАНІЗАЦІЇ НАВЧАЛЬНОЇ РОБОТИ СТУДЕНТІВ ТЕХНІЧНИХ УНІВЕРСИТЕТІВ (Педагогіка вищої та середньої школи, 2022)
In the article some ways of further perfection of technical universities' students' educational work taking into consideration new conditions of education are discussed.